1996
DOI: 10.1379/1466-1268(1996)001<0237:apomci>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A pathway of multi-chaperone interactions common to diverse regulatory proteins: estrogen receptor, Fes tyrosine kinase, heat shock transcription factor Hsf1, and the aryl hydrocarbon receptor

Abstract: A variety of regulatory proteins, including different classes of transcription factors and protein kinases, have been identified in complexes with Hsp90. On careful examination of unactivated progesterone receptor complexes, eight different protein participants have been identified, and each can be considered a component of the cytoplasmic molecular chaperone machinery. These proteins are Hsp90, Hsp70, Hip, p60, p23, FKBP51, FKBP52 and Cyp40. Studies in a cell-free assembly system have helped to define a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
161
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(172 citation statements)
references
References 0 publications
10
161
1
Order By: Relevance
“…The mechanistic details of hsp90 function are still unclear. However, it does appear that similar hsp90 complexes are utilized in the maturation of a number of different target proteins (20,21). The functions of the accessory proteins that bind to hsp90 are only beginning to be understood.…”
mentioning
confidence: 99%
“…The mechanistic details of hsp90 function are still unclear. However, it does appear that similar hsp90 complexes are utilized in the maturation of a number of different target proteins (20,21). The functions of the accessory proteins that bind to hsp90 are only beginning to be understood.…”
mentioning
confidence: 99%
“…For instance, the dioxin receptor is a ligand-dependent transcription factor which, in the absence of ligand, is found in the cytoplasmic compartment of the cell or, depending on cell type, evenly distributed between the cytoplasm and the nucleus (1,2). This non-activated form of the receptor interacts with the hsp90 1 -dependent molecular chaperone complex (3) and its associated proteins, such as the hsp90-associated factor p23 (4,5) and the dioxin receptor specific immunophilin XAP-2 (6 -8).…”
mentioning
confidence: 99%
“…Another example of a differential chaperone requirement for steroid receptor activation involves Cdc37. Cdc37 is required for the folding of several protein kinases and was proposed to be kinase specific based on its failure to interact with aryl hydrocarbon receptor, estrogen receptor, GR, or PR in vitro (15)(16)(17). On the other hand, genetic studies using the yeast Saccharomyces cerevisiae as a model system showed that Cdc37 was important for hormone-dependent activity by AR but not by GR (18).…”
mentioning
confidence: 99%